2015
DOI: 10.1016/j.algal.2014.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical characterization of microalgal biomass from freshwater species isolated in Alberta, Canada for animal feed applications

Abstract: Vous avez des questions? Nous pouvons vous aider. Pour communiquer directement avec un auteur, consultez la première page de la revue dans laquelle son article a été publié afin de trouver ses coordonnées. Si vous n'arrivez pas à les repérer, communiquez avec nous à PublicationsArchive-ArchivesPublications@nrc-cnrc.gc.ca.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 88 publications
(57 citation statements)
references
References 58 publications
5
50
2
Order By: Relevance
“…Mild heating of native proteins causes disruption of secondary and tertiary structures, which allows proteins to unfold, permitting for more efficient enzymatic digestion. Although the amino acid profiles of microalgal proteins are generally high relative to other common plant proteins [9,14,31], the functional properties of algal proteins are poorly understood. Chronakis [27] demonstrated that Spirulina proteins are highly viscous at acidic pH but become less viscous and more highly soluble at higher pH levels and this could affect the results from the various in vitro protein digestion assays used.…”
Section: Monogastric Animalsmentioning
confidence: 99%
See 4 more Smart Citations
“…Mild heating of native proteins causes disruption of secondary and tertiary structures, which allows proteins to unfold, permitting for more efficient enzymatic digestion. Although the amino acid profiles of microalgal proteins are generally high relative to other common plant proteins [9,14,31], the functional properties of algal proteins are poorly understood. Chronakis [27] demonstrated that Spirulina proteins are highly viscous at acidic pH but become less viscous and more highly soluble at higher pH levels and this could affect the results from the various in vitro protein digestion assays used.…”
Section: Monogastric Animalsmentioning
confidence: 99%
“…(AB04-C-F-PLM02) and M. reisseri (AB05-C-U-BBM02). Isolation conditions, 18S gene sequence identification, screening criteria, mass cultivation, harvesting and processing and biochemical characterization are fully described in Tibbetts et al [9]. Proximate and caloric content of whole and lipidextracted biomass are presented in Table 1.…”
Section: Microalgal Biomassmentioning
confidence: 99%
See 3 more Smart Citations